Pattern classification of odour for electronic nose - Tong, Wee Chin. (2013)
This project is based on the architecture of Electronic Nose. The Electronic Nose comprises of Figaro sensors, data acquisition and pattern classification. The main part revolves around the development of the pattern classification, as this is the main objective for this project. The understanding of data acquisition is important as it is required to carry out tests on the odour. Different classification network has been considered and eventually comes to Probabilistic Neural Network (PNN).